2002
DOI: 10.1200/jco.20.6.1480
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Individuals With Germline Mutations in BRCA1 and BRCA2: Analysis of 10,000 Individuals

Abstract: Specific features of personal and family history can be used to assess the likelihood of identifying a mutation in BRCA1 or BRCA2 in individuals tested in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
486
3
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 634 publications
(528 citation statements)
references
References 28 publications
33
486
3
6
Order By: Relevance
“…These observations are in agreement with large studies on ovarian cancer patients (Risch et al, 2001;Frank et al, 2002). It has repeatedly been shown that only a small percentage of BRCA-positive ovarian cancer cases occur at ages o40 years (Boyd et al, 2000;Liede et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…These observations are in agreement with large studies on ovarian cancer patients (Risch et al, 2001;Frank et al, 2002). It has repeatedly been shown that only a small percentage of BRCA-positive ovarian cancer cases occur at ages o40 years (Boyd et al, 2000;Liede et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…All samples were analyzed for BRCA1 and BRCA2 through full gene sequencing and rearrangement testing per published protocol [42] through Myriad Genetics Laboratories Inc. This analysis identifies gene mutations in all of the known protein coding sequences and additional adjacent areas in the genes and detects approximately 90-95% of mutations in BRCA1 and BRCA2.…”
Section: Brca1 and Brca2 Analysismentioning
confidence: 99%
“…To obtain optimal ascertainment, many risk assessment models and prior probability models have been developed and evaluated (de la Hoya et al, 2003;Domchek et al, 2003). Four such models, the Claus, Gilpin, Frank and Evans model (Claus et al, 1998;Gilpin et al, 2000;Frank et al, 2002;Evans et al, 2004) are empirically derived scoring systems, easy to apply in daily practice with the use of a pencil and a paper and easy to understand for both counsellor and patient.With the Claus tables the probability of developing breast cancer can be determined, but not the likelihood of detecting a BRCA mutation (as in prior probability models). These tables are based on series of unselected women with breast cancer.…”
mentioning
confidence: 99%